A new troglobitic species of Typhloroncus (Arachnida: Pseudoscorpiones: Ideoroncidae) from Guatemala - Viana, Ana Clara M.; Ferreira, Rodrigo L. (Zootaxa, 2019)
Typhloroncus guatemalensis sp. n., found in Gruta de Lanquín, a limestone cave located in the municipality of Lanquín (Alta Verapaz, Guatemala), is described. It can be distinguished from the congeneric species mainly by the presence of lanceolate ventrodistal telotarsal setae on all legs; by the chelal teeth, which exhibit a varied morphology; by the number of trichobothria (30‒32); and by its measurements. Typhloroncus guatemalensis sp. n. represents the first record for the genus in Guatemala and is considered to be troglobitic.